Joint Estimation of Factor Sensitivities and Risk Premia for the Arbitrage Pricing Theory: Discussion - Brown, Stephen J. (Journal of Finance, 1988)
Stephen J. Brown, Joint Estimation of Factor Sensitivities and Risk Premia for the Arbitrage Pricing Theory: Discussion, The Journal of Finance, Vol. 43, No. 3, Papers and Proceedings of the Forty-Seventh Annual Meeting of the American Finance Association, Chicago, Illinois, December 28-30, 1987 (Jul., 1988), pp. 734-735